Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
29-x/21 + 27-x/23 + 25-x/25 + 23-x/27 + 21-x/29 = -5
1 + 29-x/21 + 1 + 27-x/23 + 1 + 25-x/25 + 1 + 23-x/27 + 1 + 21-x/29 = 0
50-x/21 + 50-x/23 + 50-x/25 + 50-x/27 + 50-x/29 = 0
(50-x) (1/21 + 1/23 + 1/25 + 1/27 + 1/29) = 0
Vì: 1/21 + 1/23 + 1/25 + 1/27 + 1/2 > 0
=> 50 - x = 0
x = 50
Vậy x = 50
\(\frac{-1}{3}+\frac{0,2-0,3+\frac{5}{11}}{-0,3+\frac{9}{16}-\frac{15}{12}}\)
\(=\frac{-1}{3}+\frac{\frac{2}{10}-\frac{3}{10}+\frac{5}{11}}{\frac{-3}{10}+\frac{9}{16}-\frac{15}{12}}\)
\(=\frac{-1}{3}+\frac{\frac{39}{110}}{\frac{-79}{80}}\)
\(=\frac{-1}{3}-\frac{312}{869}\)
\(=\frac{-1805}{2607}\)
\((x-6)(3x-9)>0\)
TH1:
\(\orbr{\begin{cases}x-6< 0\\3x-9< 0\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x< 6\\x< 3\end{cases}}\)\(\Rightarrow x< 3\)
TH2:
\(\orbr{\begin{cases}x-6>0\\3x-9>0\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x>6\\x>3\end{cases}}\)\(\Rightarrow x>6\)
Vậy \(x< 3\) hoặc \(x>6\)thì \((x-6)(3x-9)>0\)
Học tốt!
20.
\((2x-1)(6-x)>0\)
TH1:
\(\orbr{\begin{cases}2x-1>0\\6-x>0\end{cases}\Rightarrow\orbr{\begin{cases}x< \frac{1}{2}\\x< 6\end{cases}}\Rightarrow x< 6}\)
TH2
\(\orbr{\begin{cases}2x-1< 0\\6-x< 0\end{cases}\Rightarrow\orbr{\begin{cases}x>\frac{1}{2}\\x>6\end{cases}}\Rightarrow x>\frac{1}{2}}\)
Vậy \(x< 6\)hoặc \(x>\frac{1}{2}\)thì \((2x-1)(6-x)>0\)
\(\frac{x-23}{24}+\frac{x-23}{25}=\frac{x-23}{26}+\frac{x-23}{27}\)
\(\frac{x-23}{24}+\frac{x-23}{25}-\frac{x-23}{26}-\frac{x-23}{27}=0\)
\(\left(x-23\right)\left(\frac{1}{24}+\frac{1}{25}-\frac{1}{26}-\frac{1}{27}\right)=0\)
=> x-23=0
x=0+23
x=23. Vậy x=23
Chúc bạn học tốt!^_^
\(\frac{x-23}{24}+\frac{x-23}{25}=\frac{x-23}{26}+\frac{x-23}{27}\)
=> \(\frac{x-23}{24}+\frac{x-23}{25}-\frac{x-23}{26}-\frac{x-23}{27}=0\)
=>( x-13)(\(\frac{1}{24}+\frac{1}{25}-\frac{1}{26}-\frac{1}{27}\) = 0
ta thấy 1/24>1/25>1/26>1/27 => 1/24+1/25 - 1/ 26 - 1/17 > 0
=> x -13 = -
=> x=13
Tìm x biết
a) (x-1/2)^2=4
b) 10/1/2-(x+1/3)^2=1/1/2
c) (x-1/5)^2+17/25=26/25
d) 1/5/27+(3x-7/9)^3=24/27
a) (x - 1/2)2 = 4
<=> (x - 1/2)2 = 22
<=> x - 1/2 = -2; 2
<=> x - 1/2 = 2 hoặc x - 1/2 = -2
x = 2 + 1/2 x = -2 + 1/2
x = 5/2 x = -3/2
=> x = 5/2 hoặc x = -3/2
b) 10/1/2 - (x + 1/3)2 = 1/1/2
<=> -(x + 1/3)2 = 1/1/2 - 10/1/2
<=> -(x + 1/3)2 = 1/2 - 5
<=> -(x + 1/3)2 = -5.2 + 1/2
<=> -(x + 1/3)2 = -9/2
<=> (x + 1/3)2 = 9/2
<=> x + 1/3 = \(\sqrt{\frac{9}{2}}\) hoặc x + 1/3 = \(-\sqrt{\frac{9}{2}}\)
x = \(\frac{3\sqrt{2}}{2}\) - 1/3 x = \(-\frac{3\sqrt{2}}{2}\) -1/3
=> x = \(\frac{3\sqrt{2}}{2}\) - 1/3 hoặc x = \(-\frac{3\sqrt{2}}{2}\) -1/3
c) (x - 1/5)2 + 17/25 = 26/25
<=> (x - 1/5)2 = 26/25 - 17/25
<=> (x - 1/5)2 = (3/5)2
<=> x - 1/5 = -3/5; 3/5
<=> x - 1/5 = 3/5 hoặc x - 1/5 = -3/5
x = 3/5 + 1/5 x = -3/5 + 1/5
x = 4/5 x = -2/5
=> x = 4/5 hoặc x = -2/5
a ) x − 2 5 : 2 3 = 3 4 x − 2 5 = 3 4 . 2 3 x − 2 5 = 1 2 x = 9 10
b ) x + − 3 4 − 1 2 = 2 3 . 3 5 x + − 3 4 − 1 2 = 2 5 x + − 3 4 = 9 10 x = 33 20
c ) x − 2 7 = − 9 14 . − 4 3 x − 2 7 = 6 7 +) x − 2 7 = 6 7 x = 8 7 +) x − 2 7 = − 6 7 x = − 4 7
\(1\)) \(5-\left(10-x\right)=7\)
\(10-x=5-7\)
\(10-x=-2\)
\(x=10-\left(-2\right)\)
\(x=12\)
\(2\)) \(-32-\left(x-5\right)=0\)
\(x-5=-32-0\)
\(x-5=-32\)
\(x=-32+5\)
\(x=-27\)
1) 9-25=(7-x)-(25+7)
(7-x)-(25+7)=9-25
(7-x)-(25+7)=-16
(7-x)-32=-16
7-x=-16+32
7-x=16
x=7-16
x=-9
2) (27-514) -(486-73)+x=7
(27-514) -(486-73)+x=7
-487-413+x=7
-1011+x=7
x=7-(-1011)
x=7+1011
x=1018
3) 25+5+37-25+6-29-x=37
25+5+37-25+6-29-x=37
67-25+6-29-x=37
42+6-29-x=37
48-29-x=37
19-x=37
x=19-37
x=-18
4) 14+(-12)+x =10-/-15/+ /-3/
14+(-12)+x =10-15+3
14+(-12)+x =-5+3
14+(-12)+x =-2
2+x=-2
x=-2-2
x=-4
= 34/69 nha bn
X x 23/9 =34/27
x= 34/27: 23/9
x= 24/69